1995
DOI: 10.1177/089270579500800403
|View full text |Cite
|
Sign up to set email alerts
|

Literature Review-Effects of Hydrostatic Pressure on the Mechanical Behavior of Composite Materials

Abstract: Hydrostatic pressure can cause significant changes in the mechanical properties of composite materials. A thorough understanding of these effects is essential for the effective design of composite structures for high-pressure applications. In this report, the literature on the effects of hydrostatic pressure on the mechanical behavior of composite materials is reviewed. This includes a general description of the effects of hydrostatic pressure on unreinforced polymers and a detailed critique of the experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 43 publications
3
51
0
Order By: Relevance
“…It is thus necessary to seek an appropriate failure criterion that accounts for this variation. Based on the work of other researchers [3][4][5][6][7][8][9], the transverse stresses have been shown to have a role to play in determining the fibre-direction strength of a lamina. So it can be deduced that the failure is likely to have happened at a material point with some maximal combination of the three principal stresses.…”
Section: Fe Results and Failure Criterionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is thus necessary to seek an appropriate failure criterion that accounts for this variation. Based on the work of other researchers [3][4][5][6][7][8][9], the transverse stresses have been shown to have a role to play in determining the fibre-direction strength of a lamina. So it can be deduced that the failure is likely to have happened at a material point with some maximal combination of the three principal stresses.…”
Section: Fe Results and Failure Criterionmentioning
confidence: 99%
“…However there is still a paucity of reliable experimental data for biaxial or multiaxial load cases, especially for those involving through-thickness compression and in-plane tension, due to the cost and complexity of multiaxial testing. A number of works have investigated the unidirectional tensile strength of composites under hydrostatic pressure [3][4][5][6][7][8][9]. The results of these studies show that the strength and the failure mode of composites depend strongly on the magnitude of the hydrostatic pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Pressure increases interfacial normal and shear stresses, resulting in greater adhesion between fibres and matrix, whilst reducing the influence of flaws such as microcracks and voids [2]. The effects of hydrostatic pressure on the non-linear response of a UD composite are shown in figure 2a and b, indicating a change in the post-yield behaviour and an increase in elastic modulus.…”
Section: Constitutive Response Of Materialsmentioning
confidence: 99%
“…Furthermore, polymers and polymer-matrix composites yield at different stresses in tension and compression, while the elastic modulus increases with hydrostatic pressure [1][2][3].…”
Section: Constitutive Response Of Materialsmentioning
confidence: 99%
“…It is evident that the von Mises' and Tresca's yield criteria, which were formulated by assuming that the yielding is independent of hydrostatic pressure, are inapplicable to polymers. Previous studies [1][2][3][4][5][6] have shown that the yield strength increases approximately linearly with the hydrostatic pressure. The Drucker-Prager 7 yield criterion which takes into account the linear dependence of the yield strength on hydrostatic pressure is usually adopted and is shown below:…”
Section: Introductionmentioning
confidence: 99%